Psychosocial Stress, Epileptic-Like Symptoms and Psychotic Experiences - Bob, Petr; Touskova, Tereza Petraskova; Pec, Ondrej; Raboch, Jiri; Boutros, Nash; Lysaker, Paul (Frontiers in Psychology, 2022)
Background Current research suggests that stressful life experiences and situations create a substantive effect in the development of the initial manifestations of psychotic disorders and may influence temporo-limbic epileptic-like activity manifesting as cognitive and affective seizure-like symptoms in non-epileptic conditions. Methods The current study assessed trauma history, hair cortisol levels, epileptic-like manifestations and other psychopathological symptoms in 56 drug naive adult young women experiencing their initial occurrence of psychosis. Results Hair cortisol levels among patients experiencing their initial episode of psychosis, were significantly correlated with stress symptoms measured by Trauma Symptom Checklist-40 (r = − 0.48, p < 0.01), and complex partial seizure-like symptoms measured by the Complex Partial Seizure-Like Symptoms Inventory (r = − 0.33, p < 0.05) and LSCL-33 (r = − 0.33, p < 0.05). Hair cortisol levels were not found to be significantly correlated with symptoms of anxiety and depression measured by Beck depression Inventory and Zung Anxiety Scale. Conclusion These findings suggest a significant relationship between epileptic-like symptoms and stress responses demonstrated by patients in their first psychotic episode. These findings may suggest the potential for research to explore usefulness of anticonvulsant treatment in patients who do not respond to usual psychotropic medication.